Nilai Gaya Tekan Yang Dibutuhkan Oleh Dinding Pemecah Dalam Memecahkan Nut Pada Stasiun Ripple Mill - Herry Darmadi (President University, 2023)
Ripple mill is there at the kernel station. The function of this ripple mill is that of a breaking or breaking shell from the sawmill's core by having a centrifugal (far from the center of spin) that produces ripple mills, which releases the seed from the rotor and gives it a powerful impact that causes the shell to shatter. The principle of ripple mill is that a pinch, a grinding of beans between the gaps a cistern rotorassembly with the ripple mill plate. It's called a saw seed that feeds from above the ripple mill and gets it repeatedly between the ripple plate and the moving rotor. The pressure style is a force that tends to press or destroy material. In the industry we also employ ripple mill force, for example. The sliding voltage is a stylistic link alluding to the surface of an expanding cross-section. This study aims to know how much pressure force is needed for ripple mills during the shell- breaking process, and how much slide tension occurs to the stake in the shell- breaking process. From the research that has been done, the pressure force that wall breakers need to break the nut at 31.18 n for the process to break down properly, and the shifting tension that occurs in a stake of 0.0686 n /mm2 so that the stake can last longer in its usage of ripple mill.